Anti-inflammatory and Anti-arrhythmic Activities of 1-(Alkanoylphenoxy/ Thiophenoxy)-3-(N4-Phenylpiperazinyl) Propane - Parashar, Keshav; Starling, Sushil Kumar (Journal of Drug Delivery and Therapeutics, 2019)
Synthesis and pharmacological screening of 1-(o-, m-,p-alkanoyl-, p-benzoyl-, p-cinnamoyl-, p-α-hydroxypropyl- p- α -acetoxypropyl-, p- α-oximainopropyl-, p- α -ureidiminopropyl-phenoxy/ p-propionylthiophenoxy)-3-N4-(phenylpiperazinyl)propanes, 1-(p-propionylphenoxy)-3-substituted aminopropane, 1-(p-propionylphenoxy)-3-N4-(phenylpiperazinyl) ethane and butanes and B-(p-propionylphenoxy)-N1-(N4-phenylpiperazinyl) propionamide are reported. Some of the compounds possess Anti-inflammatory and Anti-arrhythmic activity. Keyword: pharmacological screening, Anti-inflammatory, Anti-arrhythmic activity, anti-depressant activity, IR spectra, etc.